Delineating the effects of pore structure and N-doping on CO2 adsorption using coco peat derived carbon - Soniya Mariya Varghese; Additi Roy Chowdhury; Dali Naidu Arnepalli; G. Ranga Rao (Carbon Trends, 2023)
The CO2 adsorption capacity of carbon materials depends on their structural properties and chemical nature of the functionalization of carbon networks. In this work, amorphous carbon materials are derived from coco peat by activation using KOH and melamine. These are studied to determine the relative influence of pore size distribution and N-doping effect on CO2 adsorption capacity at 298 K and 1 bar. Melamine is used as a pore-directing template and N-doping agent in the preparation of ultra-microporous carbons. The surface areas and ultra-micropore volumes of carbon materials are estimated by NLDFT method based on CO2 adsorption-desorption isotherms at 273 K which vary from 753 m2 g−1 to 1702 m2 g−1 and from 0.13 cm3 g−1 to 0.33 cm3 g−1, respectively. Contrary to many theoretical and experimental studies where N-doping in carbon is reported to have a positive impact on CO2 adsorption, the present study does not indicate any beneficial effect of nitrogen content in biomass-derived carbon while the pore size distribution has a profound effect on CO2 adsorption. A direct correlation has been observed between ultra-micropore (< 0.7 nm) volume and the CO2 adsorption capacity. This study demonstrates that pore size distribution can be tuned in coco peat-derived carbons to achieve maximum CO2 adsorption capacity of 4.8 mmol g−1 at 298 K and 1 bar. It is, therefore, possible to utilize biomass materials to generate carbons with suitable pore size distribution and pore volume for CO2 capture effectively at room temperature.